Endoscopic therapy for confirmed low-grade dysplasia in Barrett’s esophagus - Pecere, Silvia; Costamagna, Guido (Translational Gastroenterology and Hepatology; Vol 3 (October 2018): Translational Gastroenterology and Hepatology, 2018)
Barrett’s esophagus (BE) is a premalignant condition characterized by replacement of the esophageal lining with metastatic columnar epithelium. To date, the management in case of confirmed low-grade dysplasia (LGD) remains controversial. In this article we summarize the available endoscopic options and their results in terms of efficacy and safety in the treatment of confirmed LGD in BE.